2004
DOI: 10.1007/s00251-004-0727-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential regulatory sequences in the untranslated regions of the baboon MHC class Ib gene, Paan-AG, more closely resemble those in the human MHC class Ia genes than those in the class Ib gene, HLA-G

Abstract: The baboon major histocompatibility complex (MHC) class Ib gene, Paan-AG, is structurally similar to the human MHC class Ia gene, HLA-A, but exhibits characteristics similar to those of the class Ib gene HLA-G. These include limited polymorphism, alternative splicing of a single message, and restricted tissue distribution, with high expression in the placenta. In order to determine whether regulatory elements controlling expression of Paan-AG resemble those of HLA-A or HLA-G, we cloned the 5' and 3' untranslat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…This gene also has a premature stop codon and possesses an expression profile similar to that of HLA-G [40]. An equivalent has recently been described for baboons [41], suggesting that this is common to the Old World monkey lineage. Most New World monkeys examined thus far appear to lack the functional equivalents of HLA-A, -B, and -C [42].…”
Section: Nonclassical Mhc Class I Genes In Primatesmentioning
confidence: 97%
“…This gene also has a premature stop codon and possesses an expression profile similar to that of HLA-G [40]. An equivalent has recently been described for baboons [41], suggesting that this is common to the Old World monkey lineage. Most New World monkeys examined thus far appear to lack the functional equivalents of HLA-A, -B, and -C [42].…”
Section: Nonclassical Mhc Class I Genes In Primatesmentioning
confidence: 97%
“…These variable sites may be important for the regulation of HLA-G expression and may act in different ways. Polymorphisms in the proximal promoter of Paan-AG , the functional homologue of HLA-G in the Olive Baboon, have been shown to influence NF- κ B binding and transcription activity [82, 83]. However, the human variable sites may act by mechanisms differing from those described above because, generally, these variable sites do not coincide with known regulatory elements (Figure 1).…”
Section: Hla-g Transcriptional Regulationmentioning
confidence: 99%
“…We cloned the 5' and 3' untranslated regions of Paan-AG and compared it to other human MHC class I genes. Sequence comparisons showed that potential regulatory elements in Paan-AG strikingly resembled those in class Ia and differed in major respects from those in HLA-G [51]. Unlike HLA-G , which contains a partially deleted and non-functional interferon-γ stimulated response element (ISRE), Paan-AG contained an intact ISRE in the promoter.…”
Section: Paan-ag: Studies On Protein Expression and Gene Regulationmentioning
confidence: 99%
“…Unlike HLA-G , which contains a partially deleted and non-functional interferon-γ stimulated response element (ISRE), Paan-AG contained an intact ISRE in the promoter. Furthermore, studies using luciferase reporter assays showed that the Paan-AG ISRE was functional [51]. Basal activity of Paan-AG ISRE and response to interferon-γ was similar to that of class Ia MHC genes.…”
Section: Paan-ag: Studies On Protein Expression and Gene Regulationmentioning
confidence: 99%